Lemon Flavored Cleaner To Protect The Society On Large-Scale Social Restrictions In Padang City, West Sumatera Province - Ismed, Ismed; Rina, Yenrina; Tuty, Anggraini; Diana, Silvy; Efrina, Efrina (Andalasian International Journal of Social and Entrepreneurial Development, 2021)
Background: The corona pandemic has wreaked havoc all across the world, especially in Indonesia.Hand washing with soap or hand sanitizer is one approach to help prevent the transmission of the coronavirus. To aid in the prevention of the corona virus, a variety of hand sanitizers have been developed.Methodology: Therefore, hand sanitizers made from alcohol with lemon aroma have been produced anddistributed to the community around the residence of the academic community of Andalas University. Thishand sanitizer is made independently using ingredients such as alcohol, glycerin, water, hydrogen peroxideand lemon extract. Conclusion: The distributed hand sanitizer is highly accepted by the community becauseof the increasing need for personal hygiene due to the increasingly massive spread of the corona virus. It ishoped that this activity can be done continuously.